Off-label direct oral anticoagulants dosing in atrial fibrillation and venous thromboembolism is associated with higher mortality. (2nd December 2021) - Aguilar, Francisco; Lo, Kevin B.; Quintero, Eduardo E.; Torres, Ricardo J.; Hung, Wikien A.; Albano, Jeri C.; Alviz, Isabella; Rodriguez, Carlos; Garcia, Mario J.; Romero, Jorge; Slipczuk, Leandro
ABSTRACT: Background: Direct oral anticoagulants (DOAC) off-label use data is lacking. Our study aimed to assess the clinical outcomes in a racially mixed population treated for atrial fibrillation (AF) and venous thromboembolism (VTE). Methods: We retrospectively evaluated six months of DOAC prescriptions for AF or VTE treatment. Prescriptions were classified as off-label or appropriate following FDA labeling. The off-label group was sub-classified as under or overdosing. Results: Of the 1, 087 DOAC prescriptions, 67% were for AF. African Americans and Caucasians were equally represented. There were 171 (16%) inappropriate prescriptions, with 106 (62%), being underdosed. The off-label group had a higher 30-day readmissions risk (OR = 1.69, 95% CI:1.11–2.54, p = 0.012) and 1-year all-cause mortality (OR = 1.90, 95% CI:1.02–3.37, p = 0.032). There was no difference in major bleeding (OR = 1.27, 95% CI:0.63–2.37, p = 0.480) or new thromboembolism (OR = 1.27, 95% CI:0.73–2.13, p = 0.369) between the groups. Underdosing carried a higher risk of new thromboembolism (OR = 3.15, 95% CI:1.09–9.15, p = 0.024). Conclusions: One in every six patients received off-label DOACs dosing. Off-label use had increased 30-day readmissions and 1-year all-cause mortality. Underdosing was associated with a higher risk of new thromboembolism.